Pengaruh Motivasi Hedonik terhadap Impulsive Buying dan Compulsive Buying: Kasus pada pada remaja lokal Tebing Tinggi yang menggunakan Kosmetik Halal - Timbul, Markahasa (Management And Business Progress, 2024)
The transformation in consumer purchasing patterns and the corresponding factors is a pertinent issue and a captivating subject for further examination by marketers and scholars in contemporary times. Within this context, the impulsive and compulsive buying behaviors among young individuals in Tebing Tinggi who utilize halal cosmetics have become the focal point of this research endeavor. The primary objective of this study is to ascertain the potential impact of hedonic motivation on impulsive and compulsive buying tendencies. The methodology adopted involves the utilization of accidental sampling technique encompassing a total of 200 participants. The data analysis procedure employed is Structural Equation Modeling (SEM). The findings indicate a positive and noteworthy correlation between hedonic motivation and impulsive buying behavior. Moreover, there exists a constructive and significant association between impulsive buying and compulsive purchasing patterns. Conversely, hedonic motivation does not exhibit any influence on compulsive buying behavior.